English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(x+1)/(x-1)=(-12/x+3)+(8/x^2+2x-3)


I'm sure theres a simple thing I'm missing but I can't figure out how to solve this.

2006-09-26 13:19:46 · 5 answers · asked by levine 2 in Science & Mathematics Mathematics

it looks like it cut off the last part, its :x^2+2x-3

2006-09-26 13:22:56 · update #1

5 answers

Original equation:
(x+1) / (x-1) = ( -12 / (x+3) ) + ( 8 / x^2+2x-3 )

Now factor the x^2 + 2x - 3:
(x+1) / (x-1) = ( -12 / (x+3) ) + ( 8 / (x + 3)(x - 1) )

Multiply both sides by (x-1): (x cannot be 1)
(x+1) = ( -12 ( x -1 ) / ( x+3 ) ) + ( 8 / (x + 3) )

Multiply both sides by (x+3): (x cannot be -3)
(x+1)(x+3) = -12 ( x -1 ) + 8

Now simplify the right side:
(x+1)(x+3) = -12x + 12 + 8
(x+1)(x+3) = -12x + 20

Multiply through:
(x^2 + 4x + 3) = -12x + 20

Add 12x to both sides:
x^2 + 16x + 3 = 20

Subtract 20 from both sides:
x^2 + 16x -17 = 0

Now factor the left side:
(x + 17)(x - 1) = 0

That would imply answers of x = -17 and x = 1, but we already eliminated x = 1 as an option (since it would make a 0 denominator).

So the answer is x = -17.

You should double check this answer, by substituting into the original equation:
(x+1) / (x-1) = ( -12 / (x+3) ) + ( 8 / x^2+2x-3 )
((-17)+1) / ((-17)-1) = ( -12 / ((-17)+3) ) + ( 8 / (-17)^2+2(-17)-3 )
-16 / -18 = -12 / -14 + 8 / (-17)^2 - 34 - 3
8 / 9 = 6 / 7 + 8 / (289 - 37)
8 / 9 = 6 / 7 + 8 / 252
8 / 9 = 6 / 7 + 2 / 63
56 / 63 = 54 / 63 + 2 / 64
56 = 54 + 2
56 = 56 (check!)

That was rather complicated, I'd say. The key was to factor the denominator and multiply through to get just the numerators. Then it is much simpler to solve.

Anyway, the answer is x = -17

2006-09-26 13:23:29 · answer #1 · answered by Puzzling 7 · 1 0

(x+1) / (x-1) = ( -12 / (x+3) ) + ( 8 / x^2+2x-3 )

multiply both sides by x^2+2x-3=(x-1)*(x+3)

you get

(x+1)*(x+3) = -12*(x-1) +8

x^2 + 4x + 3 = -12x +12 +8

x^2 + 16X - 17 = 0

X= -17

2006-09-26 13:41:09 · answer #2 · answered by n76472 1 · 0 0

(x+1)(x+3)/((x-1)(x+3)) = (-12(x-1)+8)/((x+3)(x-1))
for x not equal 1 or -3

(x+1)(x+3) = -12x+20

x^2 +16x-17 = 0

(x+17)(x-1) = 0 . Therefore x = -17 [x=1 is already excluded]

2006-09-26 13:36:21 · answer #3 · answered by contact_patlai 1 · 0 0

You must put more spaces in your equation or it looks like this.
(x+1)/(x-1)=(-12/x+3)+(8/x^2+2...

2006-09-26 13:22:24 · answer #4 · answered by Michael M 6 · 0 0

For increasing cubic binomials the standard formula is as follows: (a + b) ^ 3 = a^3 + 3*a^2*b^a million + 3*a^a million*b^2 + b^3 on your case, a is x and b is -y^5 So (x - y^5)^3 = x^3 + 3*x^2*(-y^5)^a million + 3*x^a million*(-y^5)^2 + (-y^5)^3 Simplified: =x^3 - 3x^2*y^5 + 3x*y^10 - y^15 :D

2016-12-15 15:04:38 · answer #5 · answered by ? 4 · 0 0

fedest.com, questions and answers